Analyse de la variabilité morphométrique de Dactylogyrus heteromorphus El-Gharbi, 1994 (Monogenea : Dactylogyridae) - ALLALGUA, A; BOUCENNA, I; MENASRIA, A; BOUALLEG, C; BENSOUILAH, M; KAOUACHI, N (My University, 2022)
A study was carried out in the Ain Dalia dam to estimate the seasonal variability of the morphometric descriptors of Dactylogyrus heteromorphus,monogenean parasite of the teleost fish Luciobarbus callensis (Cyprinidae) during two seasons of the year 2021 (winter and spring). Sixteen morphometric variables of the body, attachment and copulatory organ were analysed to test the existence of differences between D. heteromorphus individuals in the winter and spring seasons. Significant differences (p<0.05) were found between the two seasons in five morphometric descriptors (body length, body width, total anchor length, distance between the sleeve and base of anchor and length of marginal hook). The other eleven variables measured (distance between handle and point, distance between guard and point, length of point, length of handle, length of guard, length of median bar, width of median bar, length of ventral bar, width of ventral bar, length of copulatory piece, width of copulatory piece) did not show any significant variation (p>0.05) between seasons